Pengaruh Lokasi Dan Word Of Mouth Terhadap Keputusan Pembelian Pada Mie Ayam Cibojong (Survei Pada Pelanggan Mie Ayam Cibojong di Kabupaten Bogor) - Ira Kamila; Chaerudin Chaerudin (Peneliti.net, 2023)
This study aims to determine, analyze, and explain how the partial and simultaneous influence of location and word of mouth on purchasing decisions at Mie Ayam Cibojong. This research uses a type of quantitative research with descriptive and verification methods. The population in this study is people who have bought cibojong chicken noodles at least once. The sample to be tested in this study amounted to 384 people with sampling using slovin. This study uses a non-probability sampling technique with a purposive technique. The data analysis technique uses scale-range analysis and path analysis with the SPSS 26 for window software analysis tool. Based on the results of the research that has been done, it shows that the correlation coefficient between the location variable and word of mouth is 0.732 at a strong correlation level. The partial effect of location (X_1) on purchasing decisions has a smaller value compared to the word of mouth variable (X_2), which is equal to 12.4%, while the word of mouth variable simultaneously has a contribution of 23.1%, simultaneously the total influence of location and word of mouth on purchasing decisions is 60.3% while the remaining 39.7% is influenced by other factors outside the scope of the research in this study.